Work Ethic in Prophetic Tradition: A Thematic Analysis of Hadith Based on Hurzberg's Two-Factor Theory - Umi Nadhiroh; Moh. Misbakhul Khoir (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
Work ethic is a universal cultural value that reflects an understanding of the purpose of work and life. Hadiths offer not only spiritual teachings but also practical guidance on honest and responsible work behavior. In the face of globalization and technological disruption, Islamic values derived from hadiths can provide a moral foundation for a productive and integrity-based work culture. This study is important in strengthening spiritually grounded work ethics and addressing the lack of moral value internalization in today’s professional environment. This research employs a qualitative library research method. Primary sources include the Qur’an and authentic hadiths from canonical collections such as Sahih Bukhari and Sahih Muslim. Secondary sources consist of scholarly literature discussing Islamic perspectives on work ethics. The analysis involves takhrij al-hadith, examination of the sanad and matn, and interpretation by classical scholars. These were further analyzed in light of Herzberg’s Two-Factor Theory, which distinguishes between hygiene factors and motivational factors in job satisfaction. The findings reveal that hadiths encouraging hard work, forbidding laziness, and promoting self-reliance are authentic and valid as legal and ethical references. This supports the view that work is not only a social obligation but also an expression of faith and self-actualization. Consistent with Herzberg’s theory, these hadiths demonstrate that job satisfaction is influenced not only by external conditions but also by deeper moral and spiritual values. Therefore, these Islamic principles remain highly relevant in shaping ethical and professional behavior in the modern workforce.